Diversification Opportunities Among Sectors of KLSE, Asean and World Markets (1986 -1996) - Rohani, Muhammad Fauzi (1998)
Rationale investors are risk averse and therefore tend to avoid risk. According to the Investment Theory, unsystematic risk or business risk can be diversified away. However, in the effort of making a sound investment decision, it is sometimes difficult to gather all required information prior to making a reliable judgment. An approach to analyse the potential for diversification opportunities is to asses the correlation of returns of stocks or stock markets. The usage of stock indices to construct correlation coefficient is consistent with the weak form of Efficient Market Hypothesis. This form dictate that the prices reflects all past price and volume data. Thus, the stock indices which represent both realized prices and volume is a suitable source of data to estimate correlation coefficients.The correlation coefficient is an appropriate tool to construct a diversified portfolio as it is directly related to the variance of portfolio returns. Results of the correlation portrays a suitable relationship for selection among the stock market indices under study. The correlation of returns can be positive or negative. The correlation coefficient magnitude suggests the degree of dependence between the indices. The findings suggest that there are opportunities to diversify within Kuala Lumpur Stock Exchange (KLSE) sectorials. Also, there are possibility to diversify internationally and among ASEAN countries.